2013
DOI: 10.1016/j.jcot.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Coracoid fracture combined with distal clavicle fracture without coracoclavicular ligament rupture: A case report

Abstract: Distal clavicle fracture accompanied by coracoid process one is a rare injury. Surgical and/or conservative treatments are proposed. We report the case of a 49-year-old woman presenting a distal clavicle fracture associated with a coracoid process one due to a fall on the left shoulder. Both injuries are treated surgically. Per operatively, and through an anterior "strap" approach, the coracoclavicular ligament was seen intact. The distal clavicle fracture was fixed with K-wires and cerclage and the coracoid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…The few reports in the literature of the simultaneous occurrence of ipsilateral distal clavicle and coracoid fractures have only been reported in adults 2,7,13,14 . To the best of our knowledge, our patient is the first report of this injury pattern in the skeletally immature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The few reports in the literature of the simultaneous occurrence of ipsilateral distal clavicle and coracoid fractures have only been reported in adults 2,7,13,14 . To the best of our knowledge, our patient is the first report of this injury pattern in the skeletally immature.…”
Section: Discussionmentioning
confidence: 99%
“…Coracoid process fractures occur infrequently 2,[6][7][8]10,13 and are often associated with other shoulder girdle injuries 2,10,13 . In the growing skeleton, the most common location of coracoid injury occurs at the physeal base 4,6,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that most Rockwood type III ACJ dislocations can be treated conservatively, with sling immobilisation and pain control, and still obtain good functional results. However, for ACJ dislocation and coracoid process fractures, if the arm is used above the horizontal plane, in active young patients or in severe displacement, surgery may be preferential to prevent cosmetic deformity and reduced function 6,11 . Literature regarding surgical management of coracoid process fractures is uncommon and largely consists of lower quality evidence such as case reports 2 .…”
Section: Typementioning
confidence: 99%